Construction materials: Strategies for teaching in architecture schools - Navarro Moreno, David; Lanzón Torres, Marcos (Estoa. Journal of the Faculty of Architecture and Urbanism, 2018)
Construction materials is a fundamental part of teaching at Architecture Bachelor’s degree. Material selection for the design and construction of facilities is based not only on aesthetic considerations but also on technical performance. Together, these impacts compromise a measure of the correct material selection. So, from the point of view of teaching construction materials there are several strategies that can be used, such as the complementation of the theoretical contents with laboratory practices, the organization of workshops and seminars or the creation of a materials library.